Exploring Fungal Abundance and WHO Fungal Priority Pathogens in Agricultural Fields: A One Health Perspective in Northeast Thailand - Chayaporn Lakmuang; Syahriar Nur Maulana Malik Ibrahim; Teeratat Kaewjon; Nattapol Kraisitudomsook; Naraporn Somboonna; Ratmanee Chanabun; Ariya Chindamporn; Nuttapon Pombubpa (Life)
Fungal pathogens prevalent in agricultural areas pose a significant risk to human health, with some exhibiting high fatality rates, as reported by the WHO Fungal Pathogen Priority List (WHO FPPL). This study investigates fungal communities in northeast Thailand’s agricultural areas, focusing on potential reservoirs of the WHO FPPL. Samples were collected from rice, cassava, rubber trees, and sugarcane fields across 18 provinces with distinct geological features. Metabarcoding of the ITS1 region and taxonomic analysis were conducted, and potential pathogens were selected according to WHO FPPL criteria. The results showed that overall fungal community richness and diversity were influenced by plant fields but not significantly different by geological features. Soil organic matter and water content affected fungal dynamics only in rubber tree fields. Fungal pathogens from the WHO FPPL were found in all four plant fields, with higher abundance in Chaiyaphum province, especially in sugarcane fields, and the lowest in Nong Bua Lam Phu. Candida tropicalis, a high-priority pathogen, was predominantly associated with rock salt features. This study underscores the need for vigilance among farmers and emphasizes the importance of confirming fungal pathogenicity.